VEGETARIAN DIET IN CHILDREN - Dana-Teodora; Carmen Oltean; Laura Mihaela Trandafir; Amalia Maria Mineata (Amaltea Medical Publishing House, 2014)
Vegetarianism may have implications on the growth of children and adolescents. There are different types of vegetarian diets: some may be suitable for children, other defi cient in essential nutrients. If a vegetarian diet is done properly and includes fortifi ed foods it can promote health and reduce risk for major chronic diseases. Restriction or exclusion of products of animal nature can lead to low intake of essential nutrients.